Gun Violence Education in Medical School: A Call to Action. Issue 3 (14th June 2022) - Barron, Avery; Hargarten, Stephen; Webb, Travis
Abstract: Issue: Gun violence is a major public health burden, adversely affecting patients, families, and communities across the United States (U.S.) and the world. To manage the burden of injury from gun violence and identify primary, secondary, and tertiary prevention strategies, physician leaders must understand the biological and psychosocial aspects of this complex problem. However, gun violence and its complexities are not widely taught in medical schools. This Observation article details why gun violence education is not being included in medical education, offers an informed, science-based model for the disease of gun violence, and suggests methods to integrate gun violence education into medical school curricula. Evidence: We surveyed the literature for articles addressing this topic and for studies on medical school education and curriculum changes. We also examined some of the resources commonly used in medical school for mention of gun violence. Finally, we conducted a query of the AAMC Curriculum Inventory to further see if gun violence is currently incorporated into participating U.S. medical schools' curricula and found that gun violence is not a topic discussed in any significant capacity at most U.S. medical schools. Only 13–18% of schools that participated in the AAMC Curriculum Inventory during the years 2015–2018 documented gun and firearm content in their curriculum. Any other disease with similar number of deaths and injuries would be considered worthy of inclusion into medical education curricula. Implications: Medical school curricula commonly adjust with the ebb and flow of disease. Although gun violence meets the classic definition of a disease and is a major cause of harm and death, it is not taught to medical students. We assert that gun violence should be taught and framed as a biopsychosocial disease, highlighting many opportunities for interventions across a team of health care providers and physician leaders. We strongly urge medical schools to evaluate their curricula, address this teaching gap, and train the next generation of physician leaders to address all aspects of gun violence.